TRADISI MEMBACA QULHUWALLAH OLEH MASYARAKAT DESA PARINGGONAN KECAMATAN ULU BARUMUN KABUPATEN PADANG LAWAS - Tongku Ali Giniting Hasibuan (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The background of this research is to depart from the reading of the Qur'an which then presents or sends its reward to people who have died by the people of Paringgonan Village, Ulu Barumun District, Padang Lawas Regency, the implementation is different from what is practiced by other villages in Ulu Barumun District. This research is a qualitative field research, using descriptive analysis methods. The purpose of this study is to, Know the practice of reading qulhuwallah carried out by the people of Paringgonan Village, knowing the views of scholars and community understanding of the tradition and knowing the implications of the qulhuwallah reading tradition. The results showed that: The practice of the tradition of reading qulhuwallah in Paringgonan Village is carried out every time there is a death, on the first, second and third nights after the death is buried. The views of Paringgonan scholars on the tradition of reading qulhuwallah are generally the same, namely encouraging people to read qulhuwallah every time there is death. Community understanding of the tradition, namely a form of help for people who have died, comforting disaster experts, and social means to stay in touch. As well as the implications of this tradition, it is able to shape the personality of the community based on Qur'anic values to always remember death, help ease the burden on mait families, and also strengthen social relations of the community so that the Qur'an is more familiar in the midst of the wider community.